Holistic Marketing Strategies That Impact The Performance of Start-Up Businesses in Chiang Mai, Thailand - Srikunchai, Supachon; Pinta, Ladda (RMUTL Journal of Business Administration and Liberal Arts, 2021)
This research investigates 1) the attitudes towards holistic marketing strategies and their results, 2) the holistic marketing strategies that impact the performance of start-up businesses in Chiang Mai, and 3) the relativity of Structural equation modelling (SEM) for start-up businesses in Chiang Mai. This quantitative research employed statistical technique (SEM) for data analysis. The study sample consisted of 400 start-up businesses in Chiang Mai. The study found that attitudes towards holistic marketing strategies and their results were at the highest The was also a proof of relativity between structural model and holistic marketing strategies that impact start-up businesses in Chiang Mai with the IOC results being Chi-Square = 79.240, p = 0.081, df = 63, CMIN/df = 1.258, GFI = 0.974, AGFI = 0.951, RMSEA = 0.025 and CFI = 0.993. Moreover, the Structural Equation Modelling (SEM) which the researcher had developed from literature review and relevant concepts and theories significantly confirmed the correlation between holistic marketing strategies variables and the performance of start-up businesses in Chiang Mai. The results showed that internal marketing was the strongest factor in creating direct effect on the performance of start-up businesses in Chiang Mai with the standardized coefficient as of 0.31. Other marketing factors the directly impacted the performance of start-up businesses in Chiang Mai included integrated Marketing, relationship Marketing and social marketing with the standardized coefficient as of 0.30, 0.22, and 0.18 respectively.